Optimization of Performance and Emissions of a Diesel Engine Fuelled with Rubber Seed-Palm Biodiesel Blends using Response Surface Method - Ibrahim Khalil, Adam; A. Rashid, A. Aziz; Suzana, Yusup; Morgan, Heikel; Hagos, F. Y. (Asian Online Journals, 2016)
The effects of engine speed and load, and fuel blend ratio on the emissions and performance of an IDI (indirect injection) diesel engine were investigated. A 50:50 vol. blend of rubber seed and palm oils was used for the biodiesel production to reduce costs and enhance properties. Oil acid was reduced from 33.4 to 1.42 mg KOH/g oil by esterification followed by a transesterification in a hydrodynamic cavitation reactor. Blends of 0- 40 vol. % biodiesel to a diesel with 10% increments were prepared. Statistical tool, BBD (Box-Behnken design) based on a RSM (response surface methodology) was used to assess the combined effects of variables on parameters such as BT (torque), BP (power), BSFC (brake specific fuel consumption), BTE (brake thermal efficiency), CO, CO2, NOx, EGT (exhaust gas temperature) and O2. The engine load was found to be the most influential parameter compared to the engine speed and fuel blend. The engine speed was found to have a strong effect on performance and emissions except on BT and O2. The fuel blend effect was less significant except for BSFC, BTE, CO and CO2. On average biodiesel blends showed lower BT (0.97- 1.6%), BP (0.94- 1.4%), BTE (0.76-1.5%) and CO (0.93-6.7%) but higher BSFC (0.93- 1.7%), CO2 (0.95- 1.1%), NOx (0.97- 1.2%), EGT (1.1- 1.3%) and O2 (0.3- 1.2%) compared to diesel fuel. An optimum desirability value of 0.96 was achieved with fuel blend of 18 % (biodiesel to diesel), engine speed of 2320 rpm and engine load of 82% for the tested IDI engine.